(untitled) (African Journal of Dairy Farming and Milk Production, 2020)
The objective of this study was to detect dairy cattle infected with Brucella abortus from Jamalpur, Rangpur districts and Central Cattle Breeding and Dairy Farm (CCBDF), Savar, Dhaka in Bangladesh. Both milk and serum samples of 510 dairy cattle were initially screened by milk ring test (MRT) and Rose Bengal Test (RBT). Twelve samples positive in both MRT and RBT were further confirmed by conventional polymerase chain reaction (PCR). The overall prevalence of brucellosis based on MRT and RBT was 2.7 and 2.4%, respectively. The prevalence of brucellosis was found to be significantly (p<0.001) higher in CCBDF than Jamalpur district. Out of 7 MRT and RBT positive samples, 42.9% samples of CCBDF were PCR positive and none of the five samples of Jamalpur and Rangpur districts was PCR positive. These results strongly suggest that the use of MRT, RBT and PCR technique could lead to more reliable diagnosis of brucellosis from dairy cow in Bangladesh.